Reacción de la bolsa brasileña a las notas explicativas del COVID-19 en los estados financieros del sector agropesquero de B3 - Costa Ribeiro Prates, Juliana (2023)
In 2020, due to macroeconomic changes such as oil prices and the COVID-19 pandemic, the Circuit Breaker (CB) was activated in the Brazilian market to contain market volatility. Several sectors were negatively affected; however, the agribusiness sector recorded an increase in the volume of commodity exports. Thus, it is relevant to evaluate the performance of companies associated with the Brazilian agroindustrial sector, since it is a cross-cutting sector that involves different production chains in the country, in addition to identifying the behavior of investors in this period not only of insecurity and risk, but also of increased investments. Therefore, the objective of this study is to analyze the differences in stock returns in 2020, considering the companies in the agro-fishery sector that have published explanatory notes on COVID-19 in 2020. Monthly and daily return data of four companies have been analyzed, with a total of 96 and 132 observations respectively. The event study methodology and the Mann-Whitney test were used. The results indicate that there are no statistically significant differences between the returns in the two periods investigated and in the disclosure of information the market quickly incorporated the information in the stock prices. In addition, it is worth noting that optimistic information stood out in relation to pessimistic information. The main contribution of this study is to highlight the usefulness of this disclosure mechanism as a means of ensuring market tranquility during the global pandemic crisis and corporate welfare.